Common Stochastic Trends in a System of Exchange Rates - BAILLIE, RICHARD T.; BOLLERSLEV, TIM (Journal of Finance, 1989)
ABSTRACT Univariate tests reveal strong evidence for the presence of a unit root in the univariate time‐series representation for seven daily spot and forward exchange rate series. Furthermore, all seven spot and forward rates appear to be cointegrated; that is, the forward premiums are stationary, and one common unit root, or stochastic trend, is detectable in the multivariate time‐series models for the seven spot and forward rates, respectively. This is consistent with the hypothesis that the seven exchange rates possess one long‐run relationship and that the disequilibrium error around that relationship partly accounts for subsequent movements in the exchange rates.